Market power assessment in electricity markets based on social network analysis. (September 2021) - Beni, Sadegh Amani; Sheikh-El-Eslami, Mohammad-Kazem
Highlights: Market equilibrium model with/without a network and generation constraints are addressed. A comprehensive approach for market power detection based on social network analysis (SNA) is proposed. The novel structural and behavioral market power indices are proposed based on SNA Centrality indices. The proposed indices are compared with basic market power indices by using the Spearman correlation index. The first use of the SNA in power market is provided for market power detection. Abstract: In a non-competitive electricity market environment, market players, especially generation companies (GenCos) try to act strategically and exercise market power. Therefore, it is essential for regulators to monitor the strategic behavior of market participants. This paper proposes a comprehensive approach for market power detection based on a centrality concept in social network analysis (SNA). The proposed centrality-based indices are employed to develop structural and behavioral market power measures. Moreover, these indices are compared with basic market power indicators (share, Residual Supplier Index (RSI), and Entropy) using the Spearman correlation index to evaluate their effectiveness. The proposed method is tested on IEEE 30 bus standard test system and the proposed indices are calculated for both supply-side and demand-side participants. The obtained results show that SNA can be used as an effective tool for monitoring the market power in future smart grids with plenty of players and complexity. Graphical abstract: Image, graphical abstract